The Influence of Auditor Switching, Size of Public Accounting Office, and Company Size on Audit Delay in Automotive Companies on the Indonesia Stock Exchange, 2017 To 2021 - Febriyanti Eka Sari; Joko Suyono (NAROTAMA UNIVERSITY, Indonesia, 2023)
This study aims to analyze the effect of auditor switching, the size of a public accounting firm and company size on audit delays in automotive companies on the Indonesia Stock Exchange in 2017 - 2021. This study uses a quantitative approach using secondary data in the form of financial reports for automotive companies listed on the stock exchange. Indonesia Effect from 2017 to 2021. The sample selection technique used in this study used a purposive sampling approach, the number of samples used in this study were 44 samples. In this research the results of testing the first hypothesis (H1) show that auditor switching has an effect on audit delay, the results of testing the second hypothesis (H2) show that KAP size does not affect audit delay, The results of testing the third hypothesis (H3) show that company size has an effect on audit delay, The results of testing the fourth hypothesis (H4) show that auditor switching, KAP size and company size simultaneously influence audit delay. In this study, the difficulty of the problem lies in the independent variables used, namely auditor switching, the size of the public accounting firm and the size of the company. The dependent variable used is audit delay. In this study, researchers used automotive companies listed on the Indonesia Stock Exchange from 2017 to 2021. This research is expected to provide information and insight regarding the effect of auditor switching, the size of the public accounting firm and the size of the company on audit delay. This Paper is Original Research paper